Rachunkowość zarządcza w ochronie środowiska - Szczypa, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Management accounting instruments can be used in the area of environmental protection and through the information generated by these instruments they can help reduce the risk of running a business. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 419-426